Improving Acceptability and Uptake Behavior for Internet-Based Cognitive-Behavioral Therapy - Molloy, Anthony; Ellis, Donovan M.; Su, Langting; Anderson, Page L. (Frontiers in Digital Health, 2021)
Internet-based cognitive behavioral therapy (iCBT) programs have the potential to improve access to mental healthcare, but they are not viewed as acceptable nor widely utilized by the general public. This study tested whether two acceptance-facilitating interventions improved acceptability and uptake-related behavior for therapist assisted and self-guided iCBT. Participants were randomly assigned to read a treatment rationale for iCBT (vs. a brief definition) and to receive a small financial incentive (or not) for seeking more information about evidence-based iCBT programs. Participants (N = 662) were a diverse group recruited from a university participant pool and the surrounding community. Participants completed standardized measures of attitudes towards and outcome expectancy for iCBT and a single question about willingness to use it and were given the opportunity to get information about accessing evidence-based iCBT programs. A series of MANCOVAs showed small, positive effects of the treatment rationale on attitudes and outcome expectancy for both self-guided and therapist-assisted iCBT, but not for willingness to use it. A hierarchical logistic regression model found no effect of the treatment rationale or financial incentive on whether participants sought additional information about how to access iCBT, although psychopathology symptoms and identifying as White or multiracial were positively associated with information-seeking. Inconsistent with past research, participants rated therapist-assisted and self-guided iCBT as equally acceptable. Participants recruited from the community reported greater willingness to use iCBT than university students. These results underscore the urgent need for further research towards improving the acceptability and uptake of iCBT so that it may better fulfill its potential to fill the gap in unmet mental health need.